Er 3+/Yb 3+ codoped oxyfluoride borosilicate glass ceramic containing NaYF 4 nanocrystals for amorphous silicon solar cells - Zhao, S.; Xu, S.; Jia, Guohua; Deng, D.; Huang, L.; Wang, H. (Elsevier BV, 2011)
Transparent oxyfluoride borosilicate glass ceramic containing cubic NaYF 4 nanocrystals were successfully fabricated. The cubic NaYF 4 nanocrystals with average size of 30 nm were precipitated in the glass matrix, which was confirmed by the X-ray diffraction and TEM results. In comparison with the as-made glass, significant enhancement of upconversion luminescence is observed in the Er 3+/Yb 3+ codoped transparent glass ceramic, which may be due to the variation of coordination environment of Er 3+ and Yb 3+ ions after crystallization. The high transparency, intense upconversion luminescence and the simple, low-cost fabrication process make this material exhibiting potential applications in the fields of amorphous silicon solar cells. © 2011 Elsevier B.V. All rights reserved.